Nusantara and Mitreka Satata: A Study of the Majapahit Foreign Policy in the 13th Century - Fernandes, Michael Aprillino; Luthfi, Ismail (Diponegoro University, 2023)
In stanzas thirteen to fifteen of the Kakawin Negarakertagama, the regional terms